Design and optimization of emerging interconnection and memory subsystems for future manycore architectures - Thakkar, Ishan G., author; Pasricha, Sudeep, advisor; Bohm, Wim, committee member; Jayasumana, Anura, committee member; Lear, Kevin, committee member (Colorado State University. Libraries, 2018)
With ever-increasing core count and growing performance demand of modern data-centric applications (e.g., big data and internet-of-things (IoT) applications), energy-efficient and low-latency memory accesses and data communications (on and off the chip) are becoming essential for emerging manycore computing systems. But unfortunately, due to their poor scalability, the state-of-the-art electrical interconnects and DRAM based main memories are projected to exacerbate the latency and energy costs of memory accesses and data communications. Recent advances in silicon photonics, 3D stacking, and non-volatile memory technologies have enabled the use of cutting-edge interconnection and memory subsystems, such as photonic interconnects, 3D-stacked DRAM, and phase change memory. These innovations have the potential to enhance the performance and energy-efficiency of future manycore systems. However, despite the benefits in performance and energy-efficiency, these emerging interconnection and memory subsystems still face many technology-specific challenges along with process, environment, and workload variabilities, which negatively impact their reliability overheads and implementation feasibility. For instance, with recent advances in silicon photonics, photonic networks-on-chip (PNoCs) and core-to-memory photonic interfaces have emerged as scalable communication fabrics to enable high-bandwidth, energy-efficient, and low-latency data communications in emerging manycore systems. However, these interconnection subsystems still face many challenges due to thermal and process variations, crosstalk noise, aging, data-snooping Hardware Trojans (HTs), and high overheads of laser power generation, coupling, and distribution, all of which negatively impact reliability, security, and energy-efficiency. Along the same lines, with the advent of through-silicon via (TSV) technology, 3D-stacked DRAM architectures have emerged as small-footprint main memory solutions with relatively low per-access latency and energy costs. However, the full potential of the 3D-stacked DRAM technology remains untapped due to thermal- and scaling-induced data instability, high leakage, and high refresh rate problems along with other challenges related to 3D floorplanning and power integrity. Recent advances have also enabled Phase Change Memory (PCM) as a leading technology that can alleviate the leakage and scalability shortcomings of DRAM. But asymmetric write latency and low endurance of PCM are major challenges for its widespread adoption as main memory in future manycore systems. My research has contributed several solutions that overcome multitude of these challenges and improve the performance, energy-efficiency, security, and reliability of manycore systems integrating photonic interconnects and emerging memory (3D-stacked DRAM and phase change memory) subsystems. The main contribution of my thesis is a framework for the design and optimization of emerging interconnection and memory subsystems for future manycore computing systems. The proposed framework synergistically integrates layer-specific enhancements towards the design and optimization of emerging main memory, PNoC, and inter-chip photonic interface subsystems. In addition to subsystem-specific enhancements, we also combine enhancements across subsystems to more aggressively improve the performance, energy-efficiency, and reliability for future manycore architectures.